1996
DOI: 10.1007/bf00051982
|View full text |Cite
|
Sign up to set email alerts
|

Cryptoendolithic microorganisms from Antarctic sandstone of Linnaeus Terrace (Asgard Range): diversity, properties and interactions

Abstract: Cryptoendolithic microorganisms from stratified communities in Antarctic sandstone were studied for physiological diversity and possible interactions. Cultures of 25 bacteria, five fungi, and two green algae from one boulder grew with a wide variety of organic carbon or nitrogen sources, they exhibited varied exoenzymatic activities and were psychrophilic or psychrotrophic. Many isolates excreted vitamins into the medium and were stimulated by other vitamins. Organic acid excretion and siderophore formation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…Antibiotic resistance genes are often located on plasmids that are able to be horizontally transferred into diverse bacterial popula− tions contributing to the widespread dissemination of antibiotic resistance in the en− vironment (Davison 1999;Michaud et al 2004). Antibiotic−resistant bacteria have also detected in cold environments such as sandstones in McMurdo valley, Antarc− tica (Siebert et al 1996); the Arctic permafrost subsoil in Siberia (Mindlin et al 2008); near Palmer Station, Antarctica (Miller et al 2009); West Antarctica King George Island (Wong et al 2011); glacier environments in the Arctic, Antarctic, Central Asia, North and South America (Segawa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance genes are often located on plasmids that are able to be horizontally transferred into diverse bacterial popula− tions contributing to the widespread dissemination of antibiotic resistance in the en− vironment (Davison 1999;Michaud et al 2004). Antibiotic−resistant bacteria have also detected in cold environments such as sandstones in McMurdo valley, Antarc− tica (Siebert et al 1996); the Arctic permafrost subsoil in Siberia (Mindlin et al 2008); near Palmer Station, Antarctica (Miller et al 2009); West Antarctica King George Island (Wong et al 2011); glacier environments in the Arctic, Antarctic, Central Asia, North and South America (Segawa et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance genes are often located on plasmids that are able to transfer horizontally among diverse bacterial populations, thus contributing to the widespread dissemination of antibiotic resistance in the environment (Davison 1999;Herreros et al 2005). Antibiotic resistance has also been reported among bacteria in cold environments such as Antarctic sandstone in McMurdo Valley (Siebert et al 1996), the Arctic permafrost subsoil in Siberia (Mindlin et al 2008), Antarctic King George Island (Wong et al 2011), and seawater and penguin faecal samples collected near Palmer Station, Antarctica (Miller et al 2009). A high frequency of bacteria resistant to antibiotics can be viewed as an indicator of environmental pollution (Zhang et al 2009).…”
Section: Antibiotic Resistance and Sensitivity Of The Antarctic Bacteriamentioning
confidence: 99%
“…This is mediated by antimicrobial (antibiotic) compounds which are secreted by many phyla, and these inhibit the growth and activity of competing taxa (Hibbing et al 2010). Studies of bacteria isolated from DV soils have shown they are susceptible to antibiotics in vitro (Siebert et al 1996). However, there is no information on how widespread the ability to defend against antibiotics is among DV microorganisms.…”
Section: Introductionmentioning
confidence: 99%